Standing outside on the inside : black adolescents and the construction of academic identity - Welch, Olga M. (SUNY series, social context of education., 1997)
This book presents the results of a longitudinal study of academic achievement and pre-college enrichment of disadvantaged African American adolescents in two inner-city high schools. Through its presentation and analysis of the student's perceptions of pre-college enrichment seen in relation to their definitions of scholarship and the discussion of findings related to parent and teacher involvement, this book provides fresh perspectives on the school experiences of Black adolescents and offers important insights for those involved in both the development and evaluation of enrichment programs.